Nuremberg’s Legacy Within Transitional Justice: Prosecutions Are Here to Stay - McGonigle Leyh, Brianne (2016)
A lasting legacy of the Nuremberg and Tokyo military tribunals is the assertion that individuals are subjects of international law and should be held criminally responsible for perpetrating war crimes and crimes against humanity. Building upon the Nuremberg legacy, the emergence and proliferation of modern international(ized) tribunals has ushered in a new era in international criminal justice, whereby states seek to end impunity for international crimes through criminal trials. This Article addresses the legacy of Nuremberg in transitional justice approaches. It examines the criticisms within the transitional justice field that criminal justice processes are generally ill-suited to address the social forces that characterize collective violence and the push away from criminal prosecutions towards other non-retributive processes. It argues that while post-conflict peacebuilding requires a more holistic transitional justice approach, recourse to at least some criminal prosecutions remains an enduring legacy of Nuremberg, supported by both international actors as well as victim communities